Cheltuielile sociale, între investiție multiplicatoare și modelul statului minimalist: o analiză longitudinală pentru România - Marin, Monica; Stănculescu, Manuela Sofia (Calitatea Vieții, 2024)
This article analyses the volume of public social expenditure in Romania, in line with the approach according to which budgetary allocations for social expenditures represent multiplier investments. The differentiated analysis by functions of social protection shows contrasting developments. The costs of disability benefits registered a slight decrease in 2020 compared to 2019, yet this function of social protection had one of the lowest values at the European level. The share of expenditures for family and children has increased, and the social benefits related to unemployment also expanded. Housing expenses are constant at low values. Administration costs increased substantially in Romania in the first pandemic year. The study additionally shows the importance of examining territorial disparities as a differentiated lens on the priority awarded to social protection within the local budgets of rural administrative units in Romania.